A descriptive survey on the perception of interior designers on selected Filipino space concepts related to privacy - Balderama, Kim Ellaine A.; Florendo, Raquel Baltazar (Quezon City College of Home Economics, University of the Philippines Diliman, 2010)
The research was a descriptive survey on the perception of interior designers on selected Filipino space concepts related to privacy in a selected Filipino house. The objectives of the research were to determine the perception of interior designers; to enumerate the concepts; to assess whether designers are aware of the concepts and its significance; to confirm if designers use the concepts in their designs; and to name the factors which hinder or encourage the use of the concepts. The study interpreted the perceptions of designers on Filipino design based on the literature ?The Unity of Spatial Concepts in Philippine Architecture and Other Arts? by professor Felipe M. de Leon Jr. Ten Filipino space concepts on privacy was enumerated based on the basic idea of Filipino culture that ?all things are connected?. These space concepts were then used as the grounds to determine the perceptions of interior designers. Descriptive survey with an in depth interview was the method of gathering data. In the criteria of purposive sampling, the interior designers must be licensed professionals practicing for at least three years, member of the Philippine Institute of Interior Designers, and registered within Pasig and Marikina. The survey used the Likert scale to measure the degree of agreement of the designers on the given Filipino space concepts related to privacy. A follow up interview was conducted to elaborately explain answers on the survey The result was the perception of interior designers inclined to agree on selected Filipino space concepts related to privacy. However, their awareness to the concepts is not equivalent to its practice. 60% affirmed the use of the concepts, while 40% not necessarily follow. Interior designers who do not apply the selected space concepts believe that Filipino privacy needs had changed; while designers who use the selected space concepts believe that Filipino spaces are still in the context of limited privacy.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Space (Architecture).